Eksistensi Bahasa Wolio di Kalangan Penutur Millenial di Kota Baubau - Nurhayati, Nurhayati; Ardin, Hasrida (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
Abstract As one of the 718 regional languages ​​in Indonesia, Wolio is the language spoken in the Buton Islands region. This study was conducted to determine the extent of the existence of the Wolio language in Baubau City, especially among Millennial speakers. This research is a research that applies a qualitative and quantitative approach. Qualitative data was obtained from interviews, while quantitative data was obtained from questionnaires. This study applies a sociolinguistic study of language shift and maintenance. The sample of this research is Wolio language speakers who are included in the millennial generation (born between 1981 – 1994). The results of this study indicate that currently the average active speaker of the Wolio language is over 40 years old. Only in 2 sub-districts showed a positive trend towards the use of the Wolio language among millennial speakers in the city of Baubau. Therefore, currently the status of the Wolio language in the city of Baubau can be categorized as a local language that is threatened with extinction if no improvement is made or efforts are not made to maintain the Wolio language